Are Inflammatory Markers Important for Assessing the Severity of Diabetic Polyneuropathy? - Uslu, Muhammed Fuad; Yılmaz, Mustafa (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Background and Objectives: Diabetic neuropathy (DNP) is the most common complication of diabetes mellitus (DM), and the pathogenesis of DNP involves multiple complex pathways. In this study, we aimed to evaluate whether hematologic and inflammatory parameters, the atherogenic index, and the triglyceride–glucose (TyG) index are useful for clinical use in the development and severity of diabetic polyneuropathy (DNP) in non-diabetic (Non-DM), prediabetic (Pre-DM), and diabetic (DM) patients. Materials and Methods: Patients with Non-DM (n = 62), Pre-DM (n = 97), and DM (n = 327) were included in the study, and laboratory parameters suitable for routine use were analyzed retrospectively. Various inflammatory markers, lipid profiles, and metabolic indicators were evaluated. Results: In prediabetic patients, PNP severity showed a significant positive correlation with age (p < 0.001) and glucose levels (p = 0.020) and a significant negative correlation with LDL levels (p = 0.009). In diabetic patients, there was a positive correlation between PNP severity and age (p < 0.001), neutrophils (p = 0.024), triglycerides (p = 0.012), glucose (p < 0.001), HbA1c (p < 0.001), neutrophil-to-lymphocyte ratio (NLR) (p = 0.001), glucose-to-lymphocyte ratio (GLR) (p < 0.001), triglyceride/HDL ratio (TG/HDL) (p < 0.001), TyG index (p < 0.001), and a significant negative correlation with platelet (PLT) (p < 0.001), HDL (p < 0.001), and lymphocyte-to-monocyte ratio (LMR) (p < 0.001). In addition, age (p < 0.001), GLR (p = 0.027), and TG/HDL (p < 0.001) values were positively correlated, and the TG/glucose ratio (TGR) (p = 0.018) was negatively correlated with PNP severity in Pre-DM and DM patients. Conclusions: Our study suggests that inflammatory markers and lipid indices may play an important role in determining the severity of DNP in Non-DM, Pre-DM, and DM patients. These parameters may offer a new, easy, and low-cost option for assessing the risk of diabetic polyneuropathy. © 2025 by the authors.
Keywords: atherogenic index; diabetic polyneuropathy; hematologic markers; inflammation; TyG index